Mitral valve replacement in the first three months of life. Issue 5 (November 1984) - Pollock, J C; Shawkat, S; Houston, A
Abstract : Two infants, aged 2 and 3 months, underwent mitral valve replacement with Björk-Shiley mechanical valves for severe congenital mitral regurgitation not amenable to valve repair. Both infants survived the operation and left hospital taking a low dose aspirin anticoagulant regimen. One child survived for three years without incident, but the other died at 11 months of pneumonia after valve replacement for tissue ingrowth and subsequent thrombosis.